(untitled) (Indian Journal of Arid Horticulture, 2024)
A significant diversity is available in ber germplasm in India as well in other countries which can be exploited through apposite breeding approaches. There is urgent need to develop varieties which are tolerant to fruit fly and powdery mildew. Earliness is desirable particularly in dry regions for growing ber under rainfed or limited irrigation conditions. There is a need to develop dwarfing, high yielding varieties/rootstocks, varieties suitable for high density planting and early bearing varieties having a better quality of fruits with more storage life. The variety should yield consistently with the local requirements of maturity time, tolerant to biotic and abiotic stresses- resistance to frost, insect pests, diseases, and suitable for post-harvest uses (processing, dehydration, candying). The germplasm suitable for canopy management methods and cultural practices is to be introduced and developed. There are two main bottlenecks in ber breeding programme; polyploidy and incompatibility in its cultivars. Besides these, other constraints in improvement are typical floral morphology, short period of anthesis and stigma receptivity and limited period of fruits availability, owing to these, fruit setting is very less (<10%). The hybridization/crossing protocol need to be standardized, which is also a challenge in ber breeding.